Comparing late‐onset epileptic spasm outcomes after corpus callosotomy and subsequent disconnection surgery between post‐encephalitis/encephalopathy and non‐encephalitis/encephalopathy - Takeshi Inoue; Ichiro Kuki; Takehiro Uda; Noritsugu Kunihiro; Ryoko Umaba; Saya Koh; Megumi Nukui; Shin Okazaki; Hiroshi Otsubo (Epilepsia Open, 2023)
Abstract Objective We aimed to analyze the efficiency of corpus callosotomy (CC) and subsequent disconnection surgeries in patients with late‐onset epileptic spasms (LOES) by comparing post‐encephalitis/encephalopathy (PE) and non‐encephalitis/encephalopathy (NE). We hypothesized these surgeries can control potential focal onset epileptic spasms (ES) in the NE group but not in the PE group. Methods We retrospectively included 23 patients (12 with PE and 11 with NE) who initially underwent CC and subsequent disconnection surgeries (five NE). We compared the clinical courses, seizure types, MRI, video‐EEG, epilepsy surgery, and seizure outcomes between the two groups. Results The median age of LOES onset in the PE group was 2.8 (range 1.0–10.1 years) and 2.9 years (range 1.1–12.6) in the NE group. Bilateral MRI abnormalities were observed in both groups (PE, n = 12; NE, n = 3; P < 0.05). The PE group presented ES alone (n = 2), ES + focal seizures (FS) (n = 3), ES + generalized seizures (GS) (n = 3), and ES + FS + GS (n = 4) in addition to stimulus‐induced startle seizures (SS) (n = 8) (mean 3.1 seizure types/patient). The NE group presented ES alone (n = 1), ES + FS (n = 2), and ES + FS + GS (n = 8) (mean 2.7 seizure types/patient). In the PE group, CC stopped ES (n = 1) and SS (n = 1) and achieved <50% SS (n = 3). In the NE group, CC achieved immediate ES‐free status (n = 2) and < 50% ES (n = 1), and additional disconnection surgeries subsided all seizure types (n = 3) based on lateralized interictal/ictal EEG findings. LOES was significantly remitted by surgery in the NE group (6/11 [55%]) compared with the PE group (1/12 [8%]) (P < 0.05). Significance LOES is a drug‐resistant, focal/generalized/unknown onset ES. Lateralization of ES in NE could be achieved after CC and eliminated by further disconnection surgeries because of potential focal onset ES. LOES in PE had little benefit from CC for generalized onset ES. However, CC might reduce SS in patients in the PE group with multiple seizure types.